Analisis efisiensi dan dinamika implementasi model pembelajaran flipped classroom dalam mengakselerasi kemampuan berpikir kritis dan kemandirian belajar siswa - Putra, Muhammad Fahmi Lutfiyan (Maliki Interdisciplinary Journal, 2026)
Students’ low critical thinking skills and limited face-to-face classroom duration represent chronic challenges in meeting the demands of 21st-century education. This study aims to analyze the conceptual efficiency, fundamental structural elements, and implementation dynamics of the flipped classroom model as an instructional solution to accelerate students’ critical thinking and self-regulated learning. The method employed in this study is library research by comparing, reducing, and synthesizing theoretical literature and empirical research findings related to the flipped classroom and direct learning models. The analysis results indicate that flipped learning effectively transforms the classroom from a passive center of material transfer into a space for deep cognitive stimulation through the inversion of the learning cycle. The integration of digital media during the pre-class phase grants autonomy to students to independently regulate their learning pace at home. Consequently, during face-to-face sessions, time allocation becomes significantly more efficient for personalized clinical guidance and authentic problem-solving compared to the direct learning model, which is prone to time deficits. However, the structural effectiveness of this model faces challenges such as low student time management, gaps in teachers’ technological competence, and disparities in internet stability. This study concludes that flipped learning is not merely about shifting reading activities to the home environment, but rather a reconstruction of an adaptive ecosystem that requires preventive mitigation strategies, specifically in the form of structured self-regulated learning guidelines from the inception of the program.